Патернализм - Сусак, В. (Социология: теория, методы, маркетинг, 2007)
The paper presents theoretical and operational interpretations of the concept of paternalism in a broad comparative perspective. A special attention is focused on the role of paternalism within the "liberalism/conservatism" dichotomy. Moreover, in the context of contemporary debates the author raises a question about forms and content of paternalism as the traditional society's phenomenon within the realities of modern,industrial and postmodern, postindustrial society. There is a high probability that a qualitatively new background for the presence of paternalism in the system of social relations in contemporary societies will be formed.